Fermented Alfalfa Brown Juice Significantly Stimulates the Growth and Development of Sweet Basil (Ocimum basilicum L.) Plants - Szilvia Kisvarga; Döme Barna; Szilvia Kovács; Gábor Csatári; Ibolya O. Tóth; Miklós Gábor Fári; Péter Makleit; Szilvia Veres; Tarek Alshaal; Nóra Bákonyi (Agronomy, 2020)
Fertilization management is a key issue in plant nutrition to produce plants with good quality and quantity. Deproteinized leaf juice or brown juice (BJ) is a by-product during the isolation of leaf protein from biomass crops such as alfalfa. The idea of using BJ as a biostimulant fits well in the aspect of circular economy since BJ is currently a problematic issue of the leaf protein production approach. Fractionation of one-kilogram fresh biomass results in approximately 500 cm3 BJ. Due to fast spoil of fresh BJ, if left on room temperature, it is found that fermentation of fresh BJ using lactic acid bacteria and reducing its pH increases its stability and storage on room temperature. In the present study, we examined the effect of fermented alfalfa BJ on vegetative, physiological, and anatomical properties of the versatile sweet basil (Ocimum basilicum L. ‘Bíborfelhő’) plants. Sweet basil seedlings were sprayed at different doses of fermented alfalfa BJ (i.e., 0.5%, 1.0%, and 2.5%) and tap water served as a control (0.0% BJ). The results revealed that foliar application of fermented alfalfa BJ significantly improved the biometrical features of sweet basil plants. Plants treated with fermented BJ showed significantly higher values of all the measured parameters compared to the control (0.0%), except for the number of leaves per plants where control plants (0.0%) had more leaves. However, the leaves of control plants (0.0%) were smaller than treated plants as data of leaf area showed. Fermented alfalfa BJ significantly increased the content of photosynthetic pigments (chl a and chl b), relative chlorophyll (SPAD value), lengths of stem and root, fresh masses of stem, root, and leaves, volumes of stem and root, and leaf area. Despite all rates of fermented BJ displayed higher values over control plants (0.0%), the rate of 0.5% was the best one supported by results. Application of fermented alfalfa BJ influenced the anatomical parameters as well. These findings demonstrate the possible use of fermented alfalfa BJ as a promising novel plant biostimulant.